Application of prone position in hypoxaemic patients supported by veno-venous ECMO. (October 2018) - Lucchini, Alberto; De Felippis, Christian; Pelucchi, Giulia; Grasselli, Giacomo; Patroniti, Nicolò; Castagna, Luigi; Foti, Giuseppe; Pesenti, Antonio; Fumagalli, Roberto
Abstract: Introduction: Veno-Venous Extracorporeal Membrane Oxygenation (VV-ECMO) is an advanced respiratory care therapy allowing replacement of pulmonary gas exchange. Despite VV-ECMO support, some patients may remain hypoxaemic. A possible therapeutic procedure for these patients is the application of prone positioning. Objective: The primary aim of the present study was to investigate modification of the PaO2 /FiO2 ratio, in VV-ECMO patients with refractory hypoxaemia. The secondary aim was to evaluate the safety and feasibility of prone positioning for patients with severe Adult Respiratory Distress Syndrome supported by ECMO. Methods: We retrospectively reviewed the electronic records and charts of all patients supported by VV-ECMO who experienced at least one pronation. Complications related with prone positioning were also recorded. First PaO2 /FiO2 ratio was analysed during four different time steps: before pronation, one hour after pronation, at the end of pronation and one hour after returning to supine. Results: A total of 45 prone positioning manoeuvers were performed in 14 VV-ECMO patients from November 2009 to November 2014. The median duration of prone positioning cycles was 8 hours (IQR 6–10). No accidental dislodgement of intravascular lines, endotracheal tubes, chest tubes or a decrease in ECMO blood flow was observed. During the first prone positioning for each patient, the median PaO2 /FiO2 ratio recorded was 123 (IQR 82–135), 152 (93–185), 149 (90–186) and 113 (74–182), during PRE-supine step, 1 h-prone positioning step, END-prone positioning step, and POST-supine step respectively. Conclusions: The application of prone positioning during VV-ECMO has shown to be a safe and reliable technique when performed in a recognised ECMO centre with the appropriately trained staff and standard procedures.